Design optimization and performance analysis of deformed optical readout focal plane array. (15th May 2015) - Fu, Jianyu; Shang, Haiping; Shi, Haitao; Li, Zhigang; Yi, Ou; Chen, Dapeng; Zhang, Qingchuan
Abstract: An optical readout focal plane array (FPA) usually has a bent cantilever due to the micro-machining techniques. This bent morphology has a strong negative impact on optical sensitivity, which is a key factor that affects the imaging performance. In this study, an optical readout FPA with a stiffener-supported pixel is presented in order to reduce the deformation. The theoretical analysis has been developed to optimize the structure. Based on this, an FPA with a stiffener-supported pixel is fabricated. It is demonstrated that the curvature radius and optical sensitivity can increase by 5 times and 5.74 times respectively with respect to that without a stiffener. Better thermal imaging has been achieved.